Health Behavior, Health Knowledge, and Schooling - Kenkel, Donald S. (Journal of Political Economy, 1991)
The positive correlation between schooling and good health is well documented. One explanation is that schooling helps people choose healthier life-styles by improving their knowledge of the relationships between health behaviors and health outcomes. That is, schooling improves the household's allocative efficiency in producing health. This empirical study uses direct measures of health knowledge to test this explanation. Part of the relationship between schooling and the consumption of cigarettes, alcohol, and exercise is explained by differences in health knowledge. However, most of schooling's effects on health behavior remain after differences in knowledge are controlled for. Copyright 1991 by University of Chicago Press.